2021
DOI: 10.1073/pnas.2022472118
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and theory for lower rates of depression in larger US urban areas

Abstract: It is commonly assumed that cities are detrimental to mental health. However, the evidence remains inconsistent and at most, makes the case for differences between rural and urban environments as a whole. Here, we propose a model of depression driven by an individual’s accumulated experience mediated by social networks. The connection between observed systematic variations in socioeconomic networks and built environments with city size provides a link between urbanization and mental health. Surprisingly, this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 62 publications
(80 reference statements)
2
24
0
1
Order By: Relevance
“…1 . When including individuals living in an area with a radius larger than 78 km, we find a scaling coefficient below 1, replicating Stier et al’s result that bigger cities are protective against depression ( 1 ). However, when using city boundaries with a smaller area, we find the opposite result: a scaling coefficient above 1.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…1 . When including individuals living in an area with a radius larger than 78 km, we find a scaling coefficient below 1, replicating Stier et al’s result that bigger cities are protective against depression ( 1 ). However, when using city boundaries with a smaller area, we find the opposite result: a scaling coefficient above 1.…”
supporting
confidence: 88%
“…Specifically for scaling studies it has been shown that their results depend heavily on minimum city size inclusion criteria and the spatial extent of cities ( 6 ). Stier et al ( 1 ) address the former question using Behavioral Risk Factor Surveillance System data; here, their conclusion does not hold. When the minimum city size is lower than 600,000 inhabitants the sublinear scaling disappears.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…This study is significant in providing the evidence that gardening may increase mental resilience through the pathways of fostering “emotional regulation”, “relationship”, “confidence”, “positive thinking” and “spirituality”, with an efficacious weekly dose of between 1-4 hours. The findings may be potentially applicable to other tropical cities, as urbanites worldwide continue to find ways to cope mentally with the stressors of city living and the current Covid-19 pandemic, notwithstanding ( Stier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
“…Therefore, these “confining measures” have altered the societal norm and conditions of Singaporeans’ daily lives considerably. Lower number of social interactions reduces stimulations and choices along the dimensions of life, which may have a detrimental effect on mental health ( Stier et al, 2021 ). As a result, the feeling of loneliness may be elevated, which researchers regarded as a critical public mental health concern in the era of COVID-19 ( Killgore et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%